An Analysis Of Students’ Anxiety In Speaking Classroom At The Eleventh Grade Of SMAS Dharma Patra P.Berandan - Nudia Yultisa; Juliantina Juliantina; Muhammad Risky; Pandu Prabowo Warsodirejo; Maulidya Rahmah (Program Studi Pendidikan Biologi, 2023)
This research want to find out what is the highest rank in English speaking classroom by the internal and also the external side in SMAS Dharma Patra P.Berandan Specifically at XI Ipa 1 classroom with the population 38 students and 18 students were chosen as the samples, it purpose what factors that may contribute the highest score of anxiety in English learning environment based on the students’ perspectives. The method used in this study was qualitative method with phenomenology approach. Eighteen anxious students were selected as the participants. The data were gathered through triagulasi technique they were observation, questionnaire and also interview. In this research have two factors of anxiety they were internal such as fear of making mistake, shyness, lack of self-confidence and lack of motivation and external such as embarrassment, limited vocabulary, grammatical error, friend/classmate and also lack of preparation. Based on the internal and external factors of anxiety the result of the study showed the most influencing that make the highest rank of anxiety of students in speaking was English in class XI Ipa 1 in internal was Lack of self –confidence and the external was grammatical error that was experienced by students in English Classroom at the XI Ipa 1 SMAS Dharma Patra P.Berandan.